Earlier Formation of Noble Characters and National Character Education - Tukiran Tukiran (UM Purwokerto Press, 2023)
In this age of globalization, it has been noticed that there is a multifaceted crisis initially brought on by a moral crisis in our country. As a result, it is urgent to find ways to instill morals (akhlak) in students, youth, and university students so that they can become trustworthy citizens of their community and country in the future. The national character education is very much in accordance with noble moral education. Akhlak to Allah means refraining from idolatry and worshiping deities other than Him. Akhlak to Prophet of God includes loving and glorifying, following and obeying, and reciting shalawat and salam on him. Akhlak to parents includes serving both parents well, speaking gently, respecting them, expressing gratitude for their kindness, being devout children, and praying for them.